Antibody response and soluble mediator profile in the first six months following acute SARS-CoV-2 infection - Camila A Corsini; Priscilla S Filgueiras; Nathalie BF Almeida; Daniel AP de Miranda; Sarah VC Gomes; Adelina Junia Lourenço; Cecilia MF Bicalho; Jessica V de Assis; Raquel NH Amorim; Raphael A Silva; Raquel VR Vilela; Tulio M Lima; et al. (Scientific Reports, 2023)
Abstract The COVID-19 pandemic has caused a severe global health and economic crisis, with significant consequences for human mortality and morbidity. Therefore, there is an urgent need for more studies on the immune response to SARS-CoV-2 infection, both to enhance its effectiveness and prevent its deleterious effects. This study presents the chronology of antibodies during six months after infection in hospitalized patients and the kinetics of serum soluble mediators of the cellular response triggered by SARS-CoV-2. Samples and clinical data from 330 patients hospitalized at the Hospital da Baleia in Belo Horizonte, Brazil, who were suspected of having COVID-19, were collected at the time of hospitalization and during 6 months after infection. The immune response was analyzed by enzyme-linked immunosorbent assay (ELISA) and flow cytometry. There was a significant difference in IgM specific antibody titers from the 7th to 60th days after infection between COVID-19 negative and positive patients. Soon after 60 days after infection, antibody levels started to reduce, becoming similar to the antibody levels of the COVID-19 negative patients. IgG specific antibodies started to be detectable after 9 days of infection and antibody levels were comparatively higher in positive patients as soon as after 7 days. Furthermore, IgG levels remained higher in these patients during the complete period of 180 days after infection. The study observed similar antibody profiles between different patient groups. The soluble systemic biomarkers evaluated showed a decrease during the six months after hospitalization, except for CCL11, CXCL8, CCL3, CCL4, CCL5, IL-6, IFN-g, IL-17, IL-5, FGF-basic, PDGF, VEGF, G-CSF, and GM-CSF. The results indicate that IgM antibodies are more prominent in the early stages of infection, while IgG antibodies persist for a longer period. Additionally, the study identified that patients with COVID-19 have elevated levels of biomarkers after symptom onset, which decrease over time.